Design of general reliable multicast architecture with active network framework - Sonoda, M.; Okamura, K.; Araki, K. (15th International Conference on Information Networking (ICOIN-15 2001), 2001)
We propose a general network architecture for reliable multicast with an active network framework. Existing implementations of reliable multicast protocols have been designed over the transport layer, and have an individual retransmission control scheme. They have therefore been located in application programs, even though some protocols have been exploited for the same purpose. Our network architecture for reliable multicasting attempt to move the process to the lower application layer. Therefore the application programs do not depend on each reliable multicast protocol, so the application program can be identical, as far as the purpose of the protocols are the same. We propose the processes at the active nodes. We design the methods for these processes into the library. As a result of considering the supposed network model, we believe that the performance of our proposal is better than existing reliable multicast protocols.